Partisipasi Masyarakat Dalam Pelestarian Objek Wisata Kampung Adat Wolotopo - Marhilga Agustina Miling; Maria M. Lino; Mariayani O. Rene (Public Service and Governance Journal, 2025)
This study aims to describe the forms of community participation and analyze the supporting and inhibiting factors in the preservation of the Wolotopo Traditional Village tourism site, located in Ende Regency, East Nusa Tenggara. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observations, and documentation involving purposively selected key informants, including traditional leaders, village officials, local residents, and representatives from the Tourism Office. The findings indicate that community participation comprises four main forms: psychological (idea contribution), physical (labor), material (goods), and financial (monetary) participation. Psychological participation remains limited due to low cultural literacy and a lack of participatory space, while other forms of participation demonstrate more active community involvement in cultural and environmental preservation efforts. Supporting factors include strong social solidarity, collective programs such as the “Clean Friday” initiative, and institutional collaboration, whereas obstacles consist of inadequate infrastructure, economic dependence on the primary sector, and limited human resource capacity in tourism management. Therefore, the preservation of Wolotopo Traditional Village requires a sustainable, collaborative approach grounded in community empowerment, local economic strengthening, and the enhancement of social and cultural competencies.